2013
DOI: 10.1097/scs.0b013e3182700a03
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Intradiploic Epidermoid Cyst of Frontal Bone

Abstract: Intracranial epidermoid cysts constitute about 1% of all intracranial tumors. They are usually congenital in origin and are thought to derive from ectodermal cell inclusions occurring during closure of the neural tube. Twenty-five percent of these are found in the skull as intradiploic epidermoid cysts. These intradiploic cysts are usually congenital, slow growing, and can grow to large size without causing symptoms. We present a case of intradiploic epidermoid cyst of frontal bone developed due to childhood t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Occurrence in the parasellar region, basal cistern, sylvian fissure, pineal region and ventricle systems has also been reported [2, 13]. It has been hypothesized that IEC originates from the ectodermal tissue implanted during neural tube closure, or brought in by lumbar puncture, traumatic brain or spine injury [1, 14]. Histopathologically, EC is lined by simple or stratified squamous epithelium, covered by an outer layer of collagenous connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Occurrence in the parasellar region, basal cistern, sylvian fissure, pineal region and ventricle systems has also been reported [2, 13]. It has been hypothesized that IEC originates from the ectodermal tissue implanted during neural tube closure, or brought in by lumbar puncture, traumatic brain or spine injury [1, 14]. Histopathologically, EC is lined by simple or stratified squamous epithelium, covered by an outer layer of collagenous connective tissue.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] In this particular case, we have certainly obviated the progress of asymptomatic cyst and occurrence of potential complications. Although the cyst eroded the frontal bone, this erosion did not lead to any undesirable fracture and effect on the surgical plan of craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Formation of cyst is said to be the result of the ectodermal cell inclusions during the closure of neural tube. Twenty-five percent of intracranial cysts are located intradiploic.…”
mentioning
confidence: 99%
“…The commonest presenting complaint is a painless scalp mass,2 although they have been reported to infrequently cause symptoms related to mass effect such as headache, and more rarely cognitive or psychiatric symptoms 5. The pathophysiology of these lesions is classically attributed to congenital defects of neural tube closure, leading to ectodermal cell inclusions 2 6. Preliminary diagnoses are made preoperatively based on radiographic imaging, although histopathology is required for definitive diagnosis 7.…”
Section: Introductionmentioning
confidence: 99%
“…There are rare reports of IECs associated with trauma. The proposed mechanism for this non-congenital IEC is inoculation of epidermal cells and subsequent inflammatory reaction 3 6 12 13. To the best of the authors’ knowledge, only four cases of post-traumatic IEC have been reported 3 6 12 13…”
Section: Introductionmentioning
confidence: 99%